Survey of Access to GastroEnterology in Canada: The SAGE Wait Times Program. (2010) - Leddin, Desmond; Bridges, Ronald J; Morgan, David G; Fallone, Carlo; Render, Craig; Plourde, Victor; Gray, Jim; Switzer, Connie; McHattie, Jim; Singh, Harminder; Walli, Eric; Murray, Iain; et al.
Abstract : BACKGROUND: Assessment of current wait times for specialist health services in Canada is a key method that can assist government and health care providers to plan wisely for future health needs. These data are not readily available. A method to capture wait time data at the time of consultation or procedure has been developed, which should be applicable to other specialist groups and also allows for assessment of wait time trends over intervals of years. METHODS: In November 2008, gastroenterologists across Canada were asked to complete a questionnaire (online or by fax) that included personal demographics and data from one week on at least five consecutive new consultations and five consecutive procedure patients who had not previously undergone a procedure for the same indication. Wait times were collected for 18 primary indications and results were then compared with similar survey data collected in 2005. RESULTS: The longest wait times observed were for screening colonoscopy (201 days) and surveillance of previous colon cancer or polyps (272 days). The shortest wait times were for cancer-likely based on imaging or physical examination (82 days), severe or rapidly progressing dysphagia or odynophagia (83 days), documented iron-deficiency anemia (90 days) and dyspepsia with alarm symptoms (99 days). Compared with 2005 data, total wait times in 2008 were lengthened overall (127 days versus 155 days; P<0.05) and for most of the seven individual indications that permitted data comparison. CONCLUSION: Median wait times for gastroenterology services continue to exceed consensus conference recommended targets and have significantly worsened since 2005.